Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/bmjopen-2018-028843
|View full text |Cite
|
Sign up to set email alerts
|

Maternal adherence to micronutrient supplementation before and during pregnancy in Northwest China: a large-scale population-based cross-sectional survey

Abstract: ObjectivesTo report the situation of maternal micronutrient supplementation before and during pregnancy in Northwest China and to examine the rates of and factors related to the adherence to micronutrient supplementation among pregnant women in this region, where dietary micronutrient intake is commonly insufficient.DesignA large-scale population-based cross-sectional survey.SettingTwenty counties and ten districts of Shaanxi Province.ParticipantsA sample of 30 027 women were selected using a stratified multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 41 publications
3
42
1
Order By: Relevance
“…The high prevalence of inadequate micronutrient intake during pregnancy in our study was similar to the results of the previous studies in Northwest China [7,29]. Although micronutrient supplementation has been recommended among the pregnant women, maternal adherence to micronutrient supplementation is reported to unsatisfactory in Northwest China [8]. Diverse diet can improve nutrient status offering some benefits not provided by supplementation in pregnancy, such as easy implementation, low risk, lesser economic costs, and an improvement in maternal dietary habits [30,31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The high prevalence of inadequate micronutrient intake during pregnancy in our study was similar to the results of the previous studies in Northwest China [7,29]. Although micronutrient supplementation has been recommended among the pregnant women, maternal adherence to micronutrient supplementation is reported to unsatisfactory in Northwest China [8]. Diverse diet can improve nutrient status offering some benefits not provided by supplementation in pregnancy, such as easy implementation, low risk, lesser economic costs, and an improvement in maternal dietary habits [30,31].…”
Section: Discussionsupporting
confidence: 87%
“…Such poor diets during pregnancy are likely to be deficient in multiple micronutrients; thus, micronutrient supplementation, particularly with iron and folic acid, has been recommended among pregnant women. However, maternal adherence to micronutrient supplementation is unsatisfactory in China, especially in Northwest China [8]. Therefore, complementary strategies that address the underlying poor dietary practices are needed.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of Demographic and Health Surveys from 22 LMICs showed that while 83% of pregnant women had at least one antenatal care visit and 81% received IFA supplements during that visit, only 8% adhered to the recommended dose (defined as at least 180 tablets during the entire pregnancy) 10 . Another large‐scale survey conducted in China showed similar results, even though it used a lower cutoff to define adherence (i.e., 90 tablets), with adherence varying by micronutrient, from 0.6% for iron up to only 11.7% for calcium supplements 11 …”
Section: Introductionmentioning
confidence: 86%
“…10 Another large-scale survey conducted in China showed similar results, even though it used a lower cutoff to define adherence (i.e., 90 tablets), with adherence varying by micronutrient, from 0.6% for iron up to only 11.7% for calcium supplements. 11 Adherence has been defined as "the extent to which a patient's behavior matches the agreed recommendations from a healthcare provider." 12 Many behavior theories exist to explain the constructs related to adopting positive healthy behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Even though highly recommended since 2013, prescription of calcium supplements during pregnancy by the medical personnel remains non-systematic and is judged case by case in our setting. According to a large scale cross-sectional survey on adherence to micronutrient supplementation in pregnancy carried out in China, only 57% of pregnant women took any form of calcium supplements during their pregnancies [ 21 ]. In this study, adherence levels to calcium supplementation were as low as 11.7%.…”
Section: Introductionmentioning
confidence: 99%